"O papel de um professor estagiário no desenvolvimento de competências para a vida dos alunos" - Daniel Pereira Pinho (2021)
The Professional Internship (EP) is a curricular unit present in the last year of the Master's Degree in Physical Education Teaching in Basic and Secondary Education (MEEFEBS), of the Faculty of Sport of the University of Porto (FADEUP) and aims to place the student intern in the real context of the teaching profession in a progressive way. This curricular unit comprises two components: the Supervised Teaching Practice (PES) and the realization of an Internship Report (RE), which correspond to this document. My PES took place in two cooperating schools located in Barcelos, in the district of Braga. The internship nucleus consisted of two more student trainees (EE), a cooperating professor (PC) and an advisor professor (PO) who assisted and monitored my entire professional development process. This RE presents itself as a reflection document that intends to describe the academic and social experiences as a trainee teacher (PE) and member of the school community, as well as the strategies used by me to respond to the challenges provided in the pedagogical practice. In a first phase, these challenges relate to the first difficulties experienced as an PE, which were fundamentally related to problems of management, instruction and the creation of a motivational environment favorable to the development of learning. In a second phase, the challenge was to face a new reality, in the teaching of Physical Education at a distance. In a third and final phase, the main challenge was to implement strategies and models with the objective of making students responsible for their learning. Throughout this document, I also seek to reflect on the importance of Physical Education (PE) and how this is the only discipline capable of promoting experiences through the body and contributing to the integral development of students, in the development of their personal and social responsibility and in the development of their autonomy and active role during classes.